The Role of Public Relations in Improving Cooperative Relations With the Mass Media at the Office of The Regional Legislature of The District of Bangka - Yuni Ayu Izma; Yang Gusti Feriyanti (Jurnal Kewarganegaraan, 2025)
AbstrakPenelitian ini membahas tentang Peran Humas Dalam Meningkatkan Hubungan Kerjasama Dengan Media Massa di Kantor Dewan Perwakilan Rakyat Daerah Kabupaten Bangka. Kerjasama humas dan media massa adalah suatu kegiatan yang sangat penting untuk dilakukan dalam mempublikasikan informasi. Metode penelitian yang digunakan adalah penelitian kualitatif, teknik pengumpulan data, dengan cara observasi non partisipan, wawancara terstruktur dan dokumentasi. Hasil penelitian ini menunjukkan bahwa peran humas DPRD kabupaten Bangka dengan media massa sebagai bentuk publikasi kegiatan dalam meningkatkan citra positif para anggota dewan. Peran humas dalam meningkatkan hubungan kerjasama dengan media massa yang tertuang dalam Memorandum Of Understanding dalam bentuk surat perjanjian kerjasama mengenai pasal-pasal hukum untuk dipatuhi. Salah satu bentuk kerjasamanya berupa memberikan hasil keputusan DPRD dalam membuat rancangan peraturan daerah sesuai fungsi DPRD melalui media massa agar informasi yang disampaikan tepat sasaran kepada publik.Kata Kunci: Humas, Hubungan Kerjasama, Media Massa.Â AbstractThis research discusses the role of Public Relations in Improving Cooperation Relations with the Mass Media at the Regional House of Representatives Office of the Bangka Regency. Cooperation between public relations and mass media is an activity that is very important to do in publishing information. The research method used is qualitative research, data collection techniques, by means of non-participant observation, structured interviews and documentation. The results of this study indicate that the role of public relations for the DPRD of Bangka Regency with the mass media as a form of publication of activities in increasing the positive image of the members of the council. The role of public relations in improving cooperative relations with the mass media as stated in the Memorandum of Understanding in the form of a cooperation agreement regarding legal articles to be complied with. One form of cooperation is to provide the results of DPRD decisions in drafting regional regulations according to DPRD functions through mass media so that the information conveyed is right on target to the public. Keywords: Public Relations, Cooperation Relations, Mass Media.